Writing Strategies Utilized by Successful and Unsuccessful ESL Undergraduate Students in Writing Classroom - Kalaivaani Aluemalai; Mahendran Maniam (Journal of English Language and Culture, 2020)
The study examined the writing strategies used by undergraduate students in the ESL writing classroom. Three strategies were involved in the writing process which was; pre-writing strategies, while writing strategies and revising strategies. Specifically, the objectives were; (1) to examine the student's preferred strategies of successful and unsuccessful ESL students in the writing process. In this cross-sectional study, 50 undergraduate ESL students from Universiti Pendidikan Sultan Idris (UPSI) were the targeted sample for this study. Three strategies of the writing process; pre-writing, while writing and revising were measured via a standard questionnaire that adapted from previous studies. The data obtained were analyzed by using the software of Statistical Package for the Social Science (SPSS). The findings of this study indicated ESL students have preferred planning strategies then while writing strategies and revising strategies. Meanwhile, the findings of this study will have significant implications for ESL undergraduate students in their writing. Contributions, limitations, and implications of the study are also discussed.